Value of morphological and laboratory markers in predicting the effectiveness of cryoballoon pulmonary vein isolation in atrial fibrillation - E. N. Kalemberg; K. V. Davtyan; O. V. Blagova; A. A. Brutyan; P. D. Zlobina; M. S. Kharlap (Кардиоваскулярная терапия и профилактика)
Aim. To determine the clinical, morphological, and biochemical predictors of substrate-specific, non-vein-dependent atrial fibrillation (AF) by morphological and immunological examinations in patients with recurrent AF after pulmonary vein (PV) isolation.Material and methods. The study included 100 people (58 men and 42 women) with paroxysmal (n=89) and persistent (n=11) AF with a mean age of 58,2±9,4 years. After the primary operation, 15 people withdrew from the study due to refusal of reintervention, and 1 person withdrew due to suppuration of loop recorder bed and its explantation. A total of 100 patients underwent primary cryoballoon PV isolation with myocardial biopsy from the interventricular and interatrial septa, while 60 patients had subsequent hematoxylin-eosin and Van Gieson stains. Also, 100 patients were simultaneously implanted with ECG loop recorders for AF monitoring and blood was taken (before the intervention) for subsequent analysis of inflammation markers and antimyocardial antibodies. Patients underwent clinical observation during the year (visits after 3, 6, 12 months). Patients with relapses were referred for repeat electrophysiological examination and segmental ablation if PV ruptures were detected. After repeated intervention, the follow-up period was extended for a year with the same schedule of visits. According Two groups of patients were formed: without relapses (vein-dependent AF, group I) and with relapses (non-vein-dependent AF, group II), despite the achieved PV isolation as a result of 1 or 2 operations.Results. An analysis of morphological changes showed that an increase in AF recurrence risk by an average of 6,14 times (95% confidence interval: 1,14-47,6 (p=0,0462)) is associated with stage 2 interventricular septal fibrosis. Lymphocyte infiltration of the interventricular septum was associated with higher AF recurrence by an average of 9 times (95% confidence interval: 0,89-95,37) (p=0,0519).Among the laboratory parameters, a significantly higher concentration of the N-terminal pro-brain natriuretic peptide and a significantly lower concentration of antimyocardial antibodies were found in the group of patients with recurrent AF after LV isolation (p=0,0101).Conclusion. Inflammatory myocardium changes are an important link in the pathogenesis of AF and are associated with its recurrence.